Pubertal development in HIV-infected African children on first-line antiretroviral therapy. (13th March 2015) - Szubert, Alexander J.; Musiime, Victor; Bwakura-Dangarembizi, Mutsawashe; Nahirya-Ntege, Patricia; Kekitiinwa, Adeodata; Gibb, Diana M.; Nathoo, Kusum; Prendergast, Andrew J.; Walker, A. Sarah
<x xml:space="preserve">Abstract</x> Objectives: To estimate age at attaining Tanner stages in Ugandan/Zimbabwean HIV-infected children initiating antiretroviral therapy (ART) in older childhood and investigate predictors of delayed puberty, particularly age at ART initiation. Design: Observational analysis within a randomized trial. Methods: Tanner staging was assessed every 24 weeks from 10 years of age, menarche every 12 weeks and height every 4–6 weeks. Age at attaining different Tanner stages was estimated using normal interval regression, considering predictors using multivariable regression. Growth was estimated using multilevel models with child-specific intercepts and trajectories. Results: Median age at ART initiation was 9.4 years (inter-quartile range 7.8, 11.3) (n = 582). At the first assessment, the majority (80.2%) were in Tanner stage 1; median follow-up with staging was 2.8 years. There was a strong delaying effect of older age at ART initiation on age at attaining all Tanner stages (P < 0.05) and menarche (P = 0.02); in boys the delaying effect generally weakened with older age. There were additional significant delays associated with greater impairments in pre-ART height-for-age Z-score (P < 0.05) in both sexes and pre-ART BMI-for-age in girls (P < 0.05). There was no evidence that pre-ART immuno-suppression independently delayed puberty or menarche. However, older children/adolescents had significant growth spurts in intermediate Tanner stages, and were still significantly increasing their height when in Tanner stage 5 (P < 0.01). Conclusion: Delaying ART initiation until older childhood substantially delays pubertal development and menarche, independently of immuno-suppression. This highlights that factors other than CD4+, such as pubertal development, need consideration when making decisions about timing of ART initiation in older children.